Sulforaphane Potentiates Anticancer Effects of Doxorubicin and Cisplatin and Mitigates Their Toxic Effects - Calcabrini, Cinzia; Maffei, Francesca; Turrini, Eleonora; Fimognari, Carmela (Frontiers in Pharmacology, 2020)
With an expanding armamentarium available to treat cancer, however, came the recognition that narrow therapeutic indices and drug resistance are common and serious problems for therapeutic success. The association of anticancer therapies with natural compounds is an emerging strategy to improve the pharmaco-toxicological profile of cancer chemotherapy. Sulforaphane, a phytochemical found in cruciferous vegetables, is characterized by interesting therapeutic properties. Its beneficial role was investigated against different cancers such as breast, brain, blood, colon, lung, prostate and so forth. As examples to make the potentialities of the association chemotherapy raise, here we highlight and critically analyze the information available for two associations, each composed by a paradigmatic anticancer drug (cisplatin or doxorubicin) and sulforaphane.